1988
DOI: 10.1677/joe.0.1170019
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the intratesticular level of testosterone required for quantitative maintenance of spermatogenesis in the rat

Abstract: The amount of testosterone required for quantitative maintenance of spermatogenesis has been re-evaluated using techniques aimed at minimizing the synthesis of testosterone after removal of the testis. Adult male rats were treated with ethane dimethane-sulphonate (EDS) to destroy the Leydig cells, and were supplemented with 25, 5 or 1 mg testosterone esters by injection every 3 days for 21 days. Serum hormone levels, testicular morphology and spermatogenesis were assessed and the intratesticular levels of test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(85 citation statements)
references
References 0 publications
6
78
1
Order By: Relevance
“…Our results indicated that plasma testosterone level had a significant positive correlation with faster TSL, which seems higher in BR bucks compared with NZW bucks. These results are in agreement with Sharpe et al (1988), who found that male sexual desire and spermatogenesis process depends on the action of testosterone. In contrast, NZW bucks had significantly higher plasma cortisol and T 3 than those recorded in BR bucks breed after heat stress.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that plasma testosterone level had a significant positive correlation with faster TSL, which seems higher in BR bucks compared with NZW bucks. These results are in agreement with Sharpe et al (1988), who found that male sexual desire and spermatogenesis process depends on the action of testosterone. In contrast, NZW bucks had significantly higher plasma cortisol and T 3 than those recorded in BR bucks breed after heat stress.…”
Section: Discussionsupporting
confidence: 93%
“…There were no significant differences in food intake and body weights during the experimental period among the 3 groups. Testicularfree TS Ievels Since it is well known that spermatogenesis depends on the action of TS (Sharpe et al, 1988), we measured the intra-testicular levels of TS in the RJ-fed hamsters. As shown in Fig.1, the long-term feeding of RJ resulted in an increase in the intra-testicular TS Ievels in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting testosterone concentrations, while supraphysiological at the higher doses as reflected by hypertrophy of the prostate (data not shown), are low intratesticularly (Sharpe et al, 1988) and it is possible that considerably higher levels of testosterone approaching those found intratesticularly are required to produce an effect. However, the in-vitro culture of segments of seminiferous tubules from hypophysectomized rats at testosterone concenÂŹ trations (100 ng/ml) similar to those found in rat interstitial fluid (Turner et al, 1984;Sharpe et al, 1988) does not modify inhibin production, in keeping with earlier findings with Sertoli cell (Bicsak et al, 1987;Toebosch et al, 1988;Morris et al, 1988) and seminiferous tubule (Gonzales et al, 1988) cultures. In contrast, the in-vivo administration of testosterone to intact animals results in a dose-related fall then rise (after 7 but not 13 weeks) of serum inhibin levels.…”
Section: Discussionmentioning
confidence: 93%